Suitability of U.S. School Accreditation Standards for Saudi Secondary Public Schools: Principals’ Perspectives - Alotaibi, Sarah Hamed Zerfeel (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify the extent to which school accreditation standards in the United States of America are suitable for Saudi schools from the perspective of public secondary school principals in Riyadh. It also sought to determine the statistically significant differences in the participants’ responses regarding the suitability of U.S. school accreditation standards for Saudi schools, based on the variables of (academic qualification and years of experience in school administration). To achieve these objectives, the study employed a descriptive survey method and utilized a questionnaire for data collection. A sample of 211 male and female school principals from the Riyadh educational district was selected. The United States reached the results of the study on the extent of school accreditation standards in Saudi American schools from the perspective of public high school principals in the city of Riyadh to support the average approval. It also reached results on the existence of statistically significant differences in technical responses regarding the extent of school accreditation standards in Saudi American schools attributed to the variables: academic qualification, and the number of years of experience in school administration.
Keywords: Standards; School Accreditation; United States of America; Saudi Schools